Cotton contamination. Issue 3 (3rd July 2017) - van der Sluijs, M. H. J.; Hunter, L.
ABSTRACT: This review focusses on physical forms of contaminant including the presence, prevention and/or removal of foreign bodies, stickiness and seed-coat fragments rather than the type and quantity of chemical residues that might be present in cotton. Contamination in cotton, even if it is a single foreign fibre, can lead to the downgrading of yarn, fabric or garments, or even to the total rejection of an entire batch and can cause irreparable harm to the relationship between growers, ginners, merchants and textile and clothing mills. Contamination thus continues to be a very important cotton fibre quality parameter in the production pipeline, with countries and cotton that are perceived to be contaminated heavily discounted. At the same time, spinners are implementing various methods to detect and eliminate contamination. Given the adverse effect on processing and product quality arising from contamination, it was considered important to compile a review of published work and knowledge relating to the incidence, detection, measurement, consequences and reduction of contamination.